2010
DOI: 10.1111/j.1755-5949.2009.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium Salt (DBZIM) Reduces Gliosis in Mice Treated with Neurotoxicant 2′-CH3-MPTP

Abstract: We have recently identified a class of imidazolium salts (IMSs) with antioxidative property and can function as scavengers for radical oxygen species (ROS) [18]. Here, we investigate one of the IMSs, 1,3-bisbenzylimidazolium bromide (DBZIM), for its possible role in attenuating neurotoxicity and gliosis in the retina and the brain induced by a Parkinsonian neurtoxicant, methyl-4(2'-methylphenyl)-1,2,3,6-tetrahydropyridine (2'-CH(3) -MPTP), which is a free radical generating agent. In this study, we employ a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…With its promising antioxidative property, 16 was also demonstrated to have a possible role in attenuating neurotoxicity and gliosis in the retina and the brain, as induced by a Parkinsonian neurotoxicant, methyl-4(2 0 -methylphenyl)-1,2,3,6tetrahydropyridine (2 0 -CH 3 -MPTP), a free radical generating agent. 57 In this study, the authors employed a molecular retinal imaging method to assess the efficacy of 16. The longitudinal imaging results showed that 16 can effectively suppress the neurotoxicant-induced retinal gliosis.…”
Section: Antioxidants Antifibrous and Othersmentioning
confidence: 99%
“…With its promising antioxidative property, 16 was also demonstrated to have a possible role in attenuating neurotoxicity and gliosis in the retina and the brain, as induced by a Parkinsonian neurotoxicant, methyl-4(2 0 -methylphenyl)-1,2,3,6tetrahydropyridine (2 0 -CH 3 -MPTP), a free radical generating agent. 57 In this study, the authors employed a molecular retinal imaging method to assess the efficacy of 16. The longitudinal imaging results showed that 16 can effectively suppress the neurotoxicant-induced retinal gliosis.…”
Section: Antioxidants Antifibrous and Othersmentioning
confidence: 99%
“…In addition, circRNAs mostly comprise exons, although a few are formed by intron cyclization, which is highly conserved in interspecies evolution; such circRNAs have temporal specificity in certain tissue cell sources and different developmental stages. [96,97] Both lncRNAs and circRNAs exert their biological roles by binding to DNA, RNA, or proteins. They can act as intracellular competitive endogenous RNAs to regulate gene expression by directly interacting with miRNAs.…”
Section: Biogenesis and Function Of Circrnasmentioning
confidence: 99%
“…In addition, circRNAs mostly comprise exons, although a few are formed by intron cyclization, which is highly conserved in interspecies evolution; such circRNAs have temporal specificity in certain tissue cell sources and different developmental stages. [96,97]…”
Section: Overview Of Ncrnasmentioning
confidence: 99%
“…In the CNS, the main innate immune defence system is comprised mainly of the immunocompetent resident cells (i.e. the microglia) 63,64 . The hallmark of neurodegenerative diseases is microglial activation, which results in changes in microglial morphology from a quiescent and ramified shape (resting) towards a round amoeboid shape (activated) 65 .…”
Section: Parkinson’s Disease and Systemic Inflammationmentioning
confidence: 99%